2016
DOI: 10.3390/nu8050132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chocolate and Yerba Mate Phenolic Compounds on Inflammatory and Oxidative Biomarkers in HIV/AIDS Individuals

Abstract: Flavonoids in cocoa and yerba mate have a beneficial role on inflammation and oxidative disorders. Their effect on HIV individuals has not been studied yet, despite the high cardiovascular risk of this population. This study investigated the role of cocoa and yerba mate consumption on oxidative and inflammatory biomarkers in HIV+ individuals. A cross-over, placebo-controlled, double-blind, randomized clinical trial was conducted in 92 individuals on antiretroviral therapy for at least six months and at viral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
(55 reference statements)
0
13
0
2
Order By: Relevance
“…We also observed an increase of blood HDL concentrations after PS juice intake that was not detected within the PB condition. Recent nutrition intervention studies on polyphenol-rich foods such as olive oil [40] or dark chocolate [41] have been shown to positively affect HDL levels in humans. One possible explanation is that these polyphenol-rich foods may induce changes in the biochemical properties of the lipoprotein that contribute to its main biological function, particularly in the enhancement of the cholesterol efflux capacity [42].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an increase of blood HDL concentrations after PS juice intake that was not detected within the PB condition. Recent nutrition intervention studies on polyphenol-rich foods such as olive oil [40] or dark chocolate [41] have been shown to positively affect HDL levels in humans. One possible explanation is that these polyphenol-rich foods may induce changes in the biochemical properties of the lipoprotein that contribute to its main biological function, particularly in the enhancement of the cholesterol efflux capacity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence has shown that Yerba Mate consumption (3 g Yerba Mate diluted in 200 mL water once a day for sixty days) did not alter the inflammatory parameters like high-sensitivity C-reactive protein (hs-CRP), fibrinogen, and HDL-C levels in 92 HIV/AIDS-positive individuals. The discrepancy between basic research and clinical cases could be due to the amount of beverage offered, the concentration of bioactive compounds in Mate tea, and the metabolic conditions of specific populations [ 60 ].…”
Section: Health Benefitsmentioning
confidence: 99%
“…This issue provides an opportunity to update current knowledge about some examples of the six subclasses of the flavonoid compounds and their effects—even at molecular level—on immunity and inflammation, but also in inflammatory-mediated diseases such as insulin-resistance obesity, cardiovascular disease and even in cancer. The Special Issue contains six review papers [13,14,15,16,17,18] and eight research papers [19,20,21,22,23,24,25,26] on the current knowledge in the field. Contributions are from countries in Africa (South Africa), America (Brazil), Asia (China, Korea, Japan and Taiwan) and Europe (Germany, Spain and Switzerland).…”
mentioning
confidence: 99%
“…Nevertheless, these authors conclude that the evidence for the anti-inflammatory effects of cocoa is currently scarce, although cocoa consumption may prevent or even reduce vascular inflammation. Staying with the effects of cocoa and chocolate, this Special Issue also includes a research article [21] focused on a cross-over, placebo-controlled, double-blind, randomized clinical trial conducted in 92 patients infected with human immunodeficiency virus (HIV)—a population with a high cardiovascular risk. This study also includes another food rich in polyphenols—yerba mate.…”
mentioning
confidence: 99%
See 1 more Smart Citation